Production Decision and Coordination Mechanism of Socially Responsible Closed-Loop Supply Chain. (23rd May 2020) - Long, Xiaofeng; Ge, Jiali; Shu, Tong; Liu, Chunxia
Abstract : Corporate social responsibility (CSR) has a significant impact on the operation of enterprises. This study analyzes the production and coordination decisions of closed-loop supply chain (CLSC) by establishing two assumptions of endogenous and exogenous CSR. The results reveal that, for ordinary consumers, CSR is quantified as the parameter of consumer surplus, which has an impact on the patent licensing fee, revenue-sharing ratio, and so on, and which not only increases the sales quantity in CLSC but also creates more value for the manufacturer and the retailer. Considering endogenous CSR, the study found that the manufacturer's CSR level and the manufacturer's and the retailer's profits both increase with the proportion of CSR-sensitive consumers. In the endogenous model, the manufacturer sets a higher wholesale price and lower patent licensing fee than in the exogenous model. Perfect coordination in the two models can be achieved by setting a revenue-sharing ratio related to wholesale price and patent licensing fee. In practice, improving the social responsibility consciousness of consumers and raising enterprises' CSR level can achieve a win-win situation for revenues and social welfare.